THE REALITY OF JOB IMMERSION AMONG WORKERS IN THE DIRECTORATES OF THE IRAQI MINISTRY OF YOUTH AND SPORTS FROM THEIR POINT OF VIEW - Assist Prof. Dr. Rawia Abdulfatah Atoof Mohammed (Galaxy International Interdisciplinary Research Journal, 2023)
Job immersion is one of the factors that affect the job commitment of the individual, so the person may be immersed in her job without being committed to the organization as a whole. Therefore, the aim of the current research is to identify the reality of the level of job immersion among workers in the directorates of the Iraqi Ministry of Youth and Sports from the viewpoint of workers. The human field consisted of workers in the directorates of the Iraqi Ministry of Youth and Sports. The temporal field of the current research was between 2/9/2021 - 13/1/2022. The questionnaires were distributed in the directorates of the Iraqi Ministry of Youth and Sports. The descriptive analytical approach was used. The research community was represented by workers in the directorates of the Iraqi Ministry of Youth and Sports, as their total number reached 380. Workers in the directorates of the Iraqi Ministry of Youth and Sports, which represented the research sample, and the sample of the main experiment was 360 workers in the directorates of the Iraqi Ministry of Youth and Sports, and the exploratory experiment was 20 workers in the directorates of the Iraqi Ministry of Youth and Sports. The researcher points out that the results show that the workers consider that the functional work is important for their professional life. And that the functional work for the workers is considered an important part of the workers' personal life. And the assignment by the managers is very important for the workers because it enhances the status of the worker and her job affiliation. The researcher recommended the importance of investing time in the best and distinguished manner by the workers. The necessity of creating a correct environment for the employees and workers in the directorate in order to perpetuate the job properly. As well as holding courses and workshops in order to develop and improve the job immersion of workers within the directorates.